Where's the Money in Big Data - Li, Ping; Kedrosky, Paul; Guleri, Tim; Ehrenberg, Roger (O'Reilly Media, Inc., 2011)
The ability to collect, crunch, act upon, and share huge amounts of data disrupts nearly every industry, tearing down barriers to entry and creating entirely new businesses.